2020
DOI: 10.3390/en13112681
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Hybrid System for Imputation and Efficient Energy Demand Forecasting

Abstract: The ongoing upsurge of deep learning and artificial intelligence methodologies manifest incredible accomplishment in a broad scope of assessing issues in different industries, including the energy sector. In this article, we have presented a hybrid energy forecasting model based on machine learning techniques. It is based on the three machine learning algorithms: extreme gradient boosting, categorical boosting, and random forest method. Usually, machine learning algorithms focus on fine-tuning the hyperparamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…One possible explanation is that the positive and negative predicted values cancel each other out in the RFR algorithm. The ensemble learning algorithms (XGBoost and CatBoost) have shown potential in fields such as biology and medicine [13,[33][34][35][36]. Here, we found that CatBoost turns out to be a promising method for modeling forest AGB using remote sensing data.…”
Section: Comparison Of Model Performancementioning
confidence: 87%
See 1 more Smart Citation
“…One possible explanation is that the positive and negative predicted values cancel each other out in the RFR algorithm. The ensemble learning algorithms (XGBoost and CatBoost) have shown potential in fields such as biology and medicine [13,[33][34][35][36]. Here, we found that CatBoost turns out to be a promising method for modeling forest AGB using remote sensing data.…”
Section: Comparison Of Model Performancementioning
confidence: 87%
“…GBDT and AdaBoost are commonly used algorithms in Boosting. XGBoost and CatBoost, which are improvements of GBDT, have shown potential in fields such as biology and medicine [33][34][35][36]. Although some studies have attempted to use these methods for modeling forest properties from remote sensing data, the CatBoost method has been introduced very recently [13,37].…”
Section: Introductionmentioning
confidence: 99%
“…Their results, based on a performance index that combines coefficient of determination (R 2 ), RMSE, and MAPE (Mean Absolute Percentage Error), indicate that the random forest performance was 14-25% and 5-5.5% better than RT and SVR, respectively [11]. In 2020, Khan et al proposed hybrid machine learning methods [12][13][14] to forecast the energy demand. They developed a hybrid algorithm based on three machine learning techniques, i.e., random forest, extreme gradient boosting, and categorical boosting for energy demand forecasting.…”
Section: Previous Workmentioning
confidence: 99%
“…However, electric consumption forecasting is a challenging task due to various influencing factors such as outdoor weather conditions, size of the building, number of occupants, the economic state and comfort index of the occupant, the use of heating, ventilation, and air conditioning components (HVAC), operating schedules, and energy usage pattern of the occupant [3,4]. Electric energy consumption prediction is comprised of various temporal scales to analyze consumer electricity demands, such as hourly, sub-hourly, daily, weekly, monthly, yearly, and seasonally (Summer, Winter, and Fall) [5]. Therefore, it is beneficial to utilize data analytics to process and analyze the hidden characteristics of electrical energy consumption data that is essential for understanding the energy demands of multifamily residential buildings.…”
Section: Introductionmentioning
confidence: 99%